Impact of Lithuanian tax reform to companies results - Kalantaitė, Jovita; Subačienė, Rasa (Buhalterinės apskaitos teorija ir praktika, 2014)
Global economic crisis reached Lithuania in 2008, as a response to ongoing economic downturn, the government of the Republic of Lithuania introduced tax reform. Analysis of factors determined by the tax reform will be presented in the article. However, main arguments will concentrate on evaluation of companies activities and results as business is one of the key pillars on which Lithuanian economy is built on: taxes form a significant part of individual company’s expenses and on the other side – taxes are a main stream of revenue for the national budget.The most significant taxes in overall national budget composition could be named as the following: personal income tax, social insurance taxes, value added tax, corporate income tax, excise tax and others. In relation to the global crisis tax income has decreased significantly in year 2009 and at the end of year 2012 has still not reached the level of year 2008. However, from the company’s perspective, employees related taxes are considered as most significant as they form almost a half of total taxes paid by companies. Decrease of taxes related to payroll (personal income tax, social insurance taxes) was followed by growth of unemployment, decrease on average salary and growth of the shadow economy. Drop in GDP, inflation and decline in sales made impact on decrease of tax revenue of value added tax, as shadow economy and reduced consumption of excisable goods influenced the value of excise tax revenue. The tax revenue of corporate income tax was influenced by decline of net profit and profitability, increased number of bankruptcy.
Keywords: taxes; Lithuanian tax reform; results of companies activity